A Case of Recurrent Skin Abscesses: A Conundrum Solved after Obtaining a Thorough Sexual History - Diego P. Peralta; Aymara Y. Chang; Enrique Soto-Ruiz (Case Reports in Infectious Diseases)
Background. Despite the improvement in patient-physician communication techniques, sexuality and sexual health continue to be challenging areas for discussion during a clinical encounter. Most people are not prepared to discuss sexual matters openly as it can be perceived as negative or inappropriate. Consequently, an incomplete health assessment can result in delayed diagnosis or misdiagnosis. Case Report. We present a 33-year-old woman who developed recurrent left breast abscesses. She required multiple incision and drainage procedures in the operating room followed by antimicrobial therapy. Although she always had an initial improvement with this approach, she continued to have recurrences and development of new abscesses in other body areas. The polymicrobial nature of her recurrences prompted an extensive and costly workup to determine the nature of her condition. The cause was finally elucidated when a thorough sexual history was obtained. Poor hygiene practices during her sexual encounters were considered the cause of her recurrent abscesses. After medical therapy and modification of her sexual practices, she has not developed new recurrences for more than two years. Conclusion. Discussions on sexuality and sexual health are important parts of any clinical encounter, yet frequently forgotten or avoided. Becoming aware of their importance would avoid delayed diagnosis or misdiagnosis.